DETERMINAN KINERJA KARYAWAN PT. SMARTFREN TELECOM TBK - Kusuma, Endah Fatqur; indriastuti, ariyani (JURNAL STIE SEMARANG, 2024)
Abstract. Performance is the result of work in terms of quality and quantity achieved by an employee in carrying out their duties and responsibilities. The purpose of this research is to analyze the influence of compensation, leadership and career path on performance employee .Free variable in this research, namely compensation, leadership and career path, as well as the dependent variable, namely performance. Research population is an employee of PT. Smartfren Telecom Tbk Semarang Branch Office, with amount sample of 38 respondents. The data collection method is by distributing questionnaires to respondents. Data analysis uses multiple linear regression. Based on instrument test results data obtained results valid and reliable. Study this too has done it fulfil classical assumption test criteria. The result show that compensation, leadership and career path have a significant positive effect on employee performance.